STRATIGRAPHY REVIEW OF KUNINGAN AREA IN RELATION TO THE PETROLEUM POTENTIAL - -, Edy Sunardi (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
The West Java area is part of back arc basin comprising a number of North-South oriented half graben and sub-basin situated at the southernmost edge of the Sunda Platform. The area chosen for this study is called as Kuningan Area, located at the Bogor Trough, which has a complete sequence of rifting events. However, limited wells are available; therefore, a basin fill history could not be identified.It is predicted that this area has a hydrocarbon potential. Play concepts in the Northwest Java Basin, especially focused on syn-rift and post-rift sediments, whilst in the past they concentrated on carbonate build-ups on structural highs and the Jatibarang volcanics.In the offshore of NW Java Basin, to the north of this area, the proven oil and gas province are scattered in the several sub-basins such as Northwest Java Basin and Arjuna Basin. A number of different plays as shown in structural cross section in W-NE direction of the West Java Basin show the presence of extensive block faulting in the basement forming graben-like structures. The deposition of carbonate build-up is clearly indicated as Baturaja Formation in the lower part and Parigi Formation in the upper part. It is hoped that this configuration extends to the Kuningan Area which is mostly covered by thick Quaternary volcanic rocks.